The Implementation of Fire Emergency Response in the Central Java Oil and Gas Company - Ayu Nilasari Habibah; Irma Cahyaningrum (The Indonesian Journal of Occupational Safety and Health, 2022)
Introduction: Oil and gas business activities are one of several sectors that have a high risk of accidents, fires, explosions, and environmental pollution. This makes the company implement preparedness in the face of fire emergencies to be implemented by all workers so that the risk of fire can be minimized and the work environment is in a safe condition. The purpose of this study is to describe the fire emergency response system. Methods: This study was analyzed using a descriptive method and used a cross-sectional study design. The research location was in the Central Java Oil and Gas Company from February-April 2017. The data used were primary and secondary data with the researched variables including potential fire hazards, facilities, and fire prevention. Results: One of the potential hazards that exist is fire hazard potential. The facilities available as part of the emergency response system are an active protection system consisting of the provision of extinguishers, hydrants, fireboxes, foam chambers, water sprinkles, fire alarm systems, fire pumps, and fire cars. Meanwhile, the passive protection system consists of evacuation routes, muster points, evacuation maps, posters, and warning signs. Fire prevention consists of the formation of a fire-fighting team, training, simulation, and SOP containing technical execution. Conclusion: This oil and gas company has implemented an emergency response system especially for fires by facilitating active and passive protection facilities. The company has also established a fire suppression system as part of its fire emergency response system.Keywords: emergency response, fire, prevention, risk